Evaluation of coastal pollution in Banda Aceh based on BOD5 and DO approach. Issue 1 (November 2021) - Wisha, U J; Kurnianda, V
Abstract: The demand for preserving the aquatic environment is a top priority for the Indonesian government. The Banda Aceh coast has experienced anthropogenic developments since the 2004 tsunami hit. During the preliminary investigation in 2017, it indicated that the Banda Aceh coast had been contaminated. Here, we investigated water quality in Banda Aceh coast has been conducted during 2018-2019. We employed the Winkler titration for determining Biological Oxygen Demand (BOD5 ) and Dissolved Oxygen (DO). Furthermore, we generated spatial analysis to show the distribution of BOD5 and DO around the Banda Aceh coast. As a result, BOD5 has been decreased with the value of 1.33 mg/L. Interestingly, the increased DO value of 1.48 mg/L indicated the presence of autotroph biota producing an oxygen atom during 2018-2019. A contrary influence of BOD5 and DO on NO3- was identified, which approximately 50% concentration of nutrient determined by oxygen availability in 2018, while it was less than 5% for the 2019 survey. In conclusion, we suspect that the Banda Aceh coast is categorized as polluted waters for marine biota and tourism.